2015
DOI: 10.11152/mu.2013.2066.171.smd
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography in thyroid disease

Abstract: Thyroid elastography has become, lately, one of the main focuses in thyroid imaging. With more than one hundred papers published on this subject, the core of accumulated knowledge justifies the need for a comprehensive review on the topic. The paper presents the various elastographic techniques used for thyroid assessment. Both strain and shear wave elastography, with all their variants, are discussed. Thereafter the paper proceeds to a detailed description of the technical peculiarities, diagnostic value, lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 122 publications
(274 reference statements)
1
91
0
2
Order By: Relevance
“…As a result of the inflammatory process, temporary or permanent impairment of thyroid function usually follows. The different forms of thyroiditis may be clearly distinguished on the basis of clinical findings, a few laboratory values, and the ultrasound results [37]. US guided FNA with cytological examination is rarely needed.…”
Section: Diffuse Thyroid Disease (Dtd)mentioning
confidence: 99%
“…As a result of the inflammatory process, temporary or permanent impairment of thyroid function usually follows. The different forms of thyroiditis may be clearly distinguished on the basis of clinical findings, a few laboratory values, and the ultrasound results [37]. US guided FNA with cytological examination is rarely needed.…”
Section: Diffuse Thyroid Disease (Dtd)mentioning
confidence: 99%
“…When a thyroid nodule was identified (based on perceived contrast between the echogenicity of thyroid nodule and adjacent thyroid parenchyma), multiple transverse, and longitudinal sonograms of the nodule were obtained. Each nodule was assessed for suspicious grey scale sonographic features [1,21,29,30] including absent halo sign, microcalcification, hypoechogenicity, internal solid echotexture, tall to width ratio >1, and irregular margins (Figures 1 and 2). thyroiditis, grave's disease, and sub-acute thyroiditis), which were associated with increased thyroid parenchymal stiffness.…”
Section: Ultrasound Examination Of Thyroid Glandmentioning
confidence: 99%
“…Contrarily, shear wave elastography (SWE) is less operator-dependent and more reproducible than SE, and it provides quantitative assessment in the form of elasticity indices (E maximum , E mean , E minimum ). SWE uses focused ultrasound impulses at varying depths in tissue to induce tissue displacement and results in the generation of shear waves which propagate laterally [21]. Shear waves travel faster in harder medium than in softer counterpart, and their velocity is directly proportional to the square root of Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Sonoelastography (SE), a newer imaging tool in combination with ultrasound (also known as real time elastography [RTE]) has become one of the most important addition to the armamentarium of sonographic techniques in the last decade. [13,14] Although, not yet routinely used in urology clinical practice, previous studies have shown its usefulness in the differential diagnosis of breast, thyroid and prostate pathologies along with its role in diagnosing and staging acute appendicitis. [13][14][15][16] Sonoelastography maps the elastic property of soft tissues examined [16] which propelled us to use this technique in the evaluation of anterior urethral strictures not only for length but also for degree of spongiofibrosis and periurethral pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Although, not yet routinely used in urology clinical practice, previous studies have shown its usefulness in the differential diagnosis of breast, thyroid and prostate pathologies along with its role in diagnosing and staging acute appendicitis. [13][14][15][16] Sonoelastography maps the elastic property of soft tissues examined [16] which propelled us to use this technique in the evaluation of anterior urethral strictures not only for length but also for degree of spongiofibrosis and periurethral pathologies. [1,2,5] Hence in the present study, we sought to compare the efficacy of real-time SE with SUG and RUG in the evaluation of anterior urethral strictures.…”
Section: Introductionmentioning
confidence: 99%